(untitled) - Avellaneda, Marco (Boca Raton, Fla., 2000)
Quantitative Modeling of Derivative Securities demonstrates how to take the basic ideas of arbitrage theory and apply them - in a very concrete way - to the design and analysis of financial products. Based primarily (but not exclusively) on the analysis of derivatives, the book emphasizes relative-value and hedging ideas applied to different financial instruments. Using a "financial engineering approach," the theory is developed progressively, focusing on specific aspects of pricing and hedging and with problems that the technical analyst or trader has to consider in practice.More than just an introductory text, the reader who has mastered the contents of this one book will have breached the gap separating the novice from the technical and research literature
Keywords: Derivative securities,Options (Finance), Exotic options (Finance); Các hình thức đầu tư (tài chính)